Sensitivity, specificity and positive predictivevalue of patch testing: the more you test, the more you get? - Diepgen, Thomas L.; Coenraads, Pieter Jan (Contact dermatitis, 2000)
Pathophysiological variability affects the results of patch testing. In addition, even a minimal degree of test-imprecision due to this variability has a number of important statistical consequencies for the analysis and interpretation of any patch test data set. One such statistical phenomenon that is often overlooked is the dependance of the positive predictive value (i.e., the predictive value of a positive patch test) on sensitivity and specificity, the impact of which is heavily dependent on the proportion of truly allergic subjects that are studied. A 2nd important issue is the fact that patch testing is performed in series, which means multiple tests. If we assume, for example, a patch test series of only 10 allergens, then it can be demonstrated that there is a random probability of over 40% to find, simply by chance, for at least 1 allergen, a statistically significant difference between 2 groups of patients. Comparison of the results of series between patients calls for statistical adjustments in order to prevent erroneously positive differences and/or associations.